Determinants of Credit Disbursement by Multifinance Companies in Indonesia - Satriadi, Dharma; Siregar, Hermanto; Manurung, Adler Haymans; Zulbainarni, Nimmi (Journal of Ecohumanism, 2024)
Multifinance companies have the main business of providing credit to third parties, which is generally consumer credit but does not rule out investment credit. This paper aims to discuss credit disbursement in Multifinance companies for the period 2010 to 2023. Determinants of credit disbursed using panel data models. This study found the results that the interest margin significantly positively affects the loan disbursement. Operating costs significantly positively affect credit disbursed. Marketing costs significantly negatively affect the loan disbursement. Bond issuance significantly negatively affects credit disbursed. Economic growth significantly positively affects loans disbursed. Interest rate significantly positively affects loans disbursed. The COVID-19 period significantly positively affects loans disbursed. Risk significantly positively affects loans. Risk is a moderating variable in the Outstanding Loans model. Risk becomes a variable that strengthens the relationship between interest margins, marketing costs, bond issuance, and oil prices on loans. While the risk variable becomes a variable that weakens the relationship between the variables of operating costs, economic growth, interest rates, and the COVID-19 period on the loan disbursement variable.